Multidisciplinary: A Study of Infidelity and Domestic Violence - Aulia, Tina; Andaryuni, Lilik (International Journal on Advanced Science, Education, and Religion, 2025)
Infidelity is a form of emotional and physical violation committed by an individual who is already in a committed relationship, involving a third party outside that relationship. From a psychological perspective, infidelity is often triggered by dissatisfaction within the marriage, failure to meet emotional and sexual needs, and psychodynamic factors such as unresolved past traumas. Legally, in the Indonesian context, such behavior is referred to as “overspel” or adultery, as regulated under Article 284 of the Indonesian Criminal Code (KUHP), while in Islamic law, it is categorized into zina muhsan and zina ghairu muhsan. This study identifies eight primary causes of infidelity, ranging from marital crisis phases and the presence of a third party to personality dynamics. The consequences of infidelity are complex, spanning medical aspects (such as the transmission of diseases), psychological effects (including emotional trauma), and social impacts (such as divorce and domestic violence). Domestic violence (DV) itself is defined as physical, emotional, sexual, or economic abuse committed against family members, resulting in significant suffering and harm. According to Law No. 23 of 2004 on the Elimination of Domestic Violence in Indonesia, DV constitutes a violation of human rights and is subject to legal reporting and prosecution. This study emphasizes the importance of a multidisciplinary approach in analyzing the interrelated phenomena of infidelity and domestic violence, advocating for comprehensive social and legal support systems for victims. Employing a qualitative descriptive method, this research aims to provide a holistic depiction of infidelity and domestic violence as interconnected social and psychological issues, highlighting the urgent need for sustained preventive and rehabilitative interventions.